2008
DOI: 10.1007/s11325-008-0216-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for sleep disordered breathing in a Puerto Rican middle-aged population

Abstract: This is the first time a prevalence study for SDB is done among a representative sample of subjects of Puerto Rican origin. It is the first step in documenting how SDB affects this ethnic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Likewise, Blondet et al found in a study of middle-aged Puerto Ricans that among men with BMI < 30 kg/m 2 , 98% had high risk for OSA compared to 50% among nonobese men. In addition, the authors noted that 70% of women with BMI > 28 kg/m 2 were at high risk for OSA compared to only 28% of those with BMI < 28 kg/m 2 [42]. The prevalence of high risk for OSA among students with general obesity in our study was substantially higher (28.3%) compared to that in normal weight (4.6%) and overweight (5.4%) students.…”
Section: Discussionmentioning
confidence: 46%
“…Likewise, Blondet et al found in a study of middle-aged Puerto Ricans that among men with BMI < 30 kg/m 2 , 98% had high risk for OSA compared to 50% among nonobese men. In addition, the authors noted that 70% of women with BMI > 28 kg/m 2 were at high risk for OSA compared to only 28% of those with BMI < 28 kg/m 2 [42]. The prevalence of high risk for OSA among students with general obesity in our study was substantially higher (28.3%) compared to that in normal weight (4.6%) and overweight (5.4%) students.…”
Section: Discussionmentioning
confidence: 46%
“…In a validation study conducted in primary care settings in Europe and the US, the prevalence of high risk of SDB was found in the range of 19.9% to 66.7% . Studies from Norway, Porto Rico and USA found high risk of SDB as 24.3%, 56% and 26%; respectively . Lower prevalence figures were reported from Iran (4.98%) and Pakistan (12.4%) .…”
Section: Discussionmentioning
confidence: 94%
“…The Berlin questionnaire used in this study is a widely used, simple, validated tool for the prediction of sleep apnea risk [17].…”
Section: Discussionmentioning
confidence: 99%